Synthesis and Characterization of Poly(methyl methacrylate)/SiO2 Hybrid Membranes: Effect of Silica Contents on Membrane Structure - Muhammad Ali Zulfikar; Abdul Wahab Mohammad (Institut Teknologi Bandung, 2006)
Hybrid organic-inorganic based on poly(methyl methacrylate)/SiO2 (PMMA/silica) membranes were prepared using sol-gel technique under acidic conditions with different tetraethoxy orthosilane (TEOS) concentration. The thin membrane films were characterized using water permeability, water uptake, size porosity, Fourier Transform Infra Red (FTIR) and SEM analysis. Dispersion of particles in the nano scale was only possible with addition of TEOS above 10%. Organic-inorganic solutions with compositions varying from 100 PMMA/ TEOS 0 to 75 PMMA/25 TEOS were used to cast the asymmetric membranes. Water permeability, water up take and porosity size increase as TEOS content increases. SEM analysis showed that the membrane morphology changed from co-continuous phase to nodule structure if 10% TEOS was added, then return to co-continuous phase again when above 15% of TEOS was added.